2019
DOI: 10.1007/s00125-018-4797-6
|View full text |Cite
|
Sign up to set email alerts
|

lncRNA H19 prevents endothelial–mesenchymal transition in diabetic retinopathy

Abstract: Aims/hypothesis The pathophysiology of diabetic retinopathy is linked to hyperglycaemia and its effect on retinal microvascular tissues. The resulting endothelial injury changes the endothelial cell phenotype to acquire mesenchymal properties (i.e. endothelial-mesenchymal transition [EndMT]). Such changes can be regulated by epigenetic mechanisms, including long non-coding RNAs (lncRNAs). lncRNA H19 may influence EndMT through TGF-β. We investigated the role of H19 in regulating EndMT during diabetic retinopat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
157
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(165 citation statements)
references
References 59 publications
6
157
2
Order By: Relevance
“…lncRNAs of RNCR2, NEAT2, CDKN2B-AS1, and PVT1 have shown significant diagnostic performance in DR progression [27], and lncRNA-MALAT1 promotes neovascularization in DR through regulating the miR-125b/VE-cadherin axis [28]. lncRNA H19 prevents endothelial-mesenchymal transition in DR [29].The long non-coding RNA of maternally expressed gene 3 (lncRNA-MEG3)/miR223/NLRP3 inflammasome gene axis is thought to play a significant role in pyroptosis of endothelial cells [30]. The decrease in lncRNA-MEG3 could enhance retinal vessel dysfunction through the PI3k/Akt signaling pathway [31].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…lncRNAs of RNCR2, NEAT2, CDKN2B-AS1, and PVT1 have shown significant diagnostic performance in DR progression [27], and lncRNA-MALAT1 promotes neovascularization in DR through regulating the miR-125b/VE-cadherin axis [28]. lncRNA H19 prevents endothelial-mesenchymal transition in DR [29].The long non-coding RNA of maternally expressed gene 3 (lncRNA-MEG3)/miR223/NLRP3 inflammasome gene axis is thought to play a significant role in pyroptosis of endothelial cells [30]. The decrease in lncRNA-MEG3 could enhance retinal vessel dysfunction through the PI3k/Akt signaling pathway [31].…”
mentioning
confidence: 99%
“…lncRNAs of RNCR2, NEAT2, CDKN2B-AS1, and PVT1 have shown significant diagnostic performance in DR progression [27], and lncRNA-MALAT1 promotes neovascularization in DR through regulating the miR-125b/VE-cadherin axis [28]. lncRNA H19 prevents endothelial-mesenchymal transition in DR [29].…”
mentioning
confidence: 99%
“…In a recent study involving retinal endothelial cells exposed to glucose and a mouse model of DR, Thomas et al showed that H19 is involved in EMT in the retina. They also demonstrated hyperglycemia-induced downregulation of H19 in the vitreous humor from individuals with PDR compared to non-diabetic controls [12]. Nevertheless, it is important to note that lncRNAs have cell and tissue-specific expression [32], where they regulate homeostasis and the expression of protein-coding or other noncoding RNA genes [33].…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, we explored the potential role of H19 and GAS5 lncRNAs in T2DM and DR considering the following: 1) their implication in DM-and DR-related cellular pathways; 2) to the best of our knowledge, the circulating levels of H19 and GAS5 have not been evaluated in DM/DR in our population before; 3) although the levels of circulating lncRNAs have been associated with the development of DR [18,19], most of the previous studies focused on diabetic rat models or endothelial cells cultured in high-glucose conditions [12,20,21]. Here, we compared the plasma levels of circulating H19 and GAS5 lncRNAs of T2DM patients (with/ without DR) and healthy controls.…”
Section: Introductionmentioning
confidence: 99%
“…However, its pathogenesis is complicated and not fully understood. Previous studies suggested that a series of pathophysiological changes happened on the retina under the stimulation of persistent hyperglycemia, resulting in retinopathy [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%